Stability and instability of an outdoor illumination installation - Fröhner, Klaus‐Dieter; Li, Ze (Journal of Environmental Engineering and Landscape Management, 2004)
Stability and instability are very important for the layout of real world processes concerning safety and health esp. when planned by scientists. The long‐term investigation of stability was carried out for the last ten years on the basis of the installation and the evaluation of an ergonomically designed outdoor illumination. In the depicted dynamic situation the lighting design influences directly visual discomfort and human performance and in the end stability and instability. The improvement of the adaptation of luminance and its influence on the visual tasks after the rearrangement are presented and discussed. The effective factors on the visual capability and performance of workers, work efficiency and potential accidents in the night shift, and furthermore the accelerators and barriers for the stability of the project are analysed and discussed.Lauko apšvietimo įrangos stabilumas ir nestabilumasSantrauka. Projektuojamo lauko apšvietimo įrangos stabilumas ar nestabilumas turi įtakos darbuotojų darbo saugumui ir sveikatai. Siekiant, kad darbo sąlygos būtų palankesnės, dešimti pastarųjų metų projektuojant lauko apšvietimą buvo atliekami tyrimai. Dirbant kintamomis sąlygomis apšvietimas ne tik gali sukelti darbuotojams regėjimo diskomfortą, bet ir turi tiesioginės įtakos jų darbui. Straipsnyje analizuojama, kaip darbuotojai prisitaiko prie lauko apšvietimo, ir kokios įtakos jis turi jų darbo kokybei. Tokių tyrimų tikslas ‐ tobulinti apšvietimą, kad sumažėtų nelaimingų atsitikimų naktinėse pamainose, didėtų darbo efektyvumas.Reikšminiai žodžiai: stabilumas, apšvietimas, skaistis, regėjimo diskomfortas, žmonių darbas, geležinkelio manevravimo stotis.First Published Online: 14 Oct 2010